1994
DOI: 10.1523/jneurosci.14-09-05580.1994
|View full text |Cite
|
Sign up to set email alerts
|

Kappa 2 opioid receptors inhibit NMDA receptor-mediated synaptic currents in guinea pig CA3 pyramidal cells

Abstract: The role of the endogenous opioid peptide dynorphin (1–17) in regulating NMDA receptor-mediated synaptic currents was examined in guinea pig hippocampus. Schaffer collateral/commissural fiber-evoked NMDA synaptic currents were recorded using whole-cell patch-clamp techniques in CA3 pyramidal cells. Dynorphin was found to have dual effects on NMDA synaptic currents, increasing currents at low concentrations and decreasing currents at high concentrations. Only the inhibitory action of dynorphin was sensitive to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(35 citation statements)
references
References 43 publications
2
31
1
1
Order By: Relevance
“…On the basis of autoradiographic studies, it was reported that virtually no 1 receptor binding existed in the CA3 region of the guinea pig (Wagner et al, 1991(Wagner et al, , 1992; therefore, it was proposed that the receptor binding observed previously in s. lucidum (McLean et al, 1987) reflected the binding to 2 receptors (Caudle et al, 1994). Our electrophysiological results, however, suggest the presence of functional 1 receptors in the CA3 region.…”
Section: Discussioncontrasting
confidence: 43%
“…On the basis of autoradiographic studies, it was reported that virtually no 1 receptor binding existed in the CA3 region of the guinea pig (Wagner et al, 1991(Wagner et al, , 1992; therefore, it was proposed that the receptor binding observed previously in s. lucidum (McLean et al, 1987) reflected the binding to 2 receptors (Caudle et al, 1994). Our electrophysiological results, however, suggest the presence of functional 1 receptors in the CA3 region.…”
Section: Discussioncontrasting
confidence: 43%
“…Suramin and Reactive Blue 2 blocked both excitatory synaptic transmission to the pyramidal cells as well as the action of applied glutamate. A classical P2y-purinoceptor in the postsynaptic membrane may therefore modulate the glutamate receptors perhaps in a way similar to the modulation of these receptors by c2-opioid receptors (Caudle et al, 1994). Such a modulation may occur through several different mechanisms.…”
Section: Discussionmentioning
confidence: 98%
“…Selective antagonists to the NMDAR completely block the effects of Dyn A in producing hindlimb paralysis, loss of tail-flick reflex, decrease in spinal cord blood flow and barrel-rolling [13, 14, 15, 16, 17]. At the cellular level, Dyn A 1-17 has been shown to have an excitatory action on NMDA-mediated synaptic currents in guinea pig hippocampus [18]. These findings suggest that Dyn may bind directly to the NMDAR to activate or potentiate its function.…”
Section: Discussionmentioning
confidence: 99%